2015
DOI: 10.1007/s11270-015-2517-0
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Phenol from Synthetic and Industrial Wastewater by Potato Pulp Peroxidases

Abstract: Plant peroxidases have strong potential utility for decontamination of phenol-polluted wastewater. However, large-scale use of these enzymes for phenol depollution requires a source of cheap, abundant, and easily accessible peroxidase-containing material. In this study, we show that potato pulp, a waste product of the starch industry, contains large amounts of active peroxidases. We demonstrate that potato pulp may serve as a tool for peroxidase-based remediation of phenol pollution. The phenol removal efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 46 publications
4
26
0
Order By: Relevance
“…2). These findings are corresponding with data reported in our previous study, where it was shown that the removal of phenol by potato pulp did not exceed 55% in H 2 O 2 -unsupplemented reaction mixtures, but amounted to 99%, given that both potato pulp and H 2 O 2 were present in the reaction medium [15]. On the other hand, Wang et al [1] [2].…”
Section: 4-dcp Removal From Synthetic Wastewatersupporting
confidence: 91%
See 1 more Smart Citation
“…2). These findings are corresponding with data reported in our previous study, where it was shown that the removal of phenol by potato pulp did not exceed 55% in H 2 O 2 -unsupplemented reaction mixtures, but amounted to 99%, given that both potato pulp and H 2 O 2 were present in the reaction medium [15]. On the other hand, Wang et al [1] [2].…”
Section: 4-dcp Removal From Synthetic Wastewatersupporting
confidence: 91%
“…The above conditions are met by potato pulp-a waste product of starch industry, which production amounts to million tonnes per year in Europe. Our previous study showed, that potato pulp peroxidases were able to remove phenol from industrial and synthetic waste with high efficiency [15]. Since 2,4-DCP is characterized by higher persistency and toxicity, compared to phenol, we decided to test, whether potato pulp is a suitable material for its remediation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that direct addition of those enzymes to P&P mill effluent can facilitate the degradation of lignin species (Hakulinen 1988;Wagner and Nicell 2001;Fernandez-Fernandez et al 2013;Hossain and Ismail 2015;Kurnik et al 2015). Ko and Fan (2010) showed the feasibility of a two-step process in which laccase enzyme was used to polymerize ligninbased compounds and then the mixture was separated using membranes with a range of different pores sizes.…”
Section: Enzyme Treatmentmentioning
confidence: 99%
“…For example, potato pulp is a residue of the starch industry that contains a high level of peroxidase activity [100]; soybean seed hulls, a soybean-processing industry by-product is a rich source of peroxidases [101]; and oil palm empty fruit bunch (OPEFB) and palm oil mill effluent (POME) to produce lignocellulolytic enzymes [102]. The industrial implementation of enzymes for bioremediation depends on the availability of high amounts of low-cost material containing highly active and stable enzymes.…”
Section: Biocatalysts In Effluent Treatmentmentioning
confidence: 99%